Gamification in personnel management of sport - recreation service companies - Agnieszka Widawska-Stanisz (Kazimierz Wielki University, 2017)
The goal of this article was the presentation of the essence of gamification and focusing on the potential which is in this management tool. The special attention was paid to the possibility of creation gamification program proper for using in the case of service personnel management of sport - recreation companies, used for building the personnel engagement and motivating to more effective and productive work.